Crystal structure of the sesquihydrate of dehydroepiandrosterone propan-2-ylidene hydrazone: Participation of the hydrazonyl nitrogen atoms as acceptors in the elaborate hydrogen bond scheme - Wardell, James Lewis; Low, John Nicholson (European Journal of Chemistry, 2021)
The crystal structure of the sesquihydrate of dehydroepiandrosterone propan-2-ylidene hydrazone, [(7)2·(H2O)3], isolated from a solution of dehydroepiandrosterone propan-2-ylidene hydrazone, (7), in moist ethanol at room temperature, has been determined from data collected at 100 K. The sesquihydrate recrystallizes in the orthorhombic space group, P212121 with Z = 8. The asymmetric unit of [(7)2·(H2O)3] consists of two independent molecules of the steroid, Mol A and Mol B, and three moles of water. The six membered saturated rings, A and C, in both molecules have ideal or near ideal chair shapes, the unsaturated rings, B, have the expected half-chair shapes, while the five-membered rings, D, have envelope shapes with flaps at C114 and C214 for Mol A and Mol B, respectively. Differences in the conformations of the two molecules reside essentially completely within the hydrazonyl fragments with significantly different torsional angles, C117-N120-N121-C122 (in Mol A) and C217-N220-N221-C222 (in Mol B), of 149.19(14) and -93.08(17)°, respectively. The difference in this torsional angle is reflected in the hydrogen bonds involving the nitrogen atoms in the hydrazonyl units: it is of interest that the hydrazonyl nitrogen atoms partake as acceptors in hydrogen bonding with water molecules. The only intermolecular interactions in these molecules are hydrogen bonds -all classical O-H-O and OH···N hydrogen bonds with just one exception, a C-H···O(water) hydrogen bond. Of interest, there are no direct steroid-steroid links: molecules are linked solely by hydrogen bonds involving the hydrate molecules. All three hydrate molecules take part in the indirect linking of the steroid molecules, but each has its own set of contacts.